Interplay Between the Pituitary-Adrenal Axis and Thyroid Hormones in Acute-on-Chronic Liver Failure: Mechanisms, Prognostic, and Therapeutic Implications [Review] - Mahmoud A. Khattab; Yossef I. Moussa; Esraa A. Elmagid; Mohamed M. Seddik; Ahmed M. Mady; Ali M. Hamdy; Hend M. Moness (International Journal of Medical Toxicology and Legal Medicine, 2024)
Acute-on-chronic liver failure (ACLF) is a critical syndrome marked by the rapid deterioration of liver function in patients with underlying chronic liver disease, often leading to multi-organ failure and high short-term mortality. This review illustrates the interactions between the hypothalamic-pituitary-adrenal (HPA) axis and thyroid hormone metabolism in ACLF. Endocrine disruptions, including adrenal insufficiency and non-thyroidal illness syndrome (NTIS), are common and associated with increased disease severity and poorer outcomes. These hormonal imbalances contribute to systemic inflammation and organ dysfunction, highlighting their potential as prognostic markers and therapeutic targets. The review discusses the prevalence, diagnostic challenges, and treatment outcomes of adrenal and thyroid dysfunctions in ACLF and considers the inclusion of endocrine failure in ACLF diagnostic criteria. Future research should focus on elucidating the mechanisms of endocrine dysregulation and validating effective hormonal therapies in ACLF.